Profil Penalaran Siswa SMP dalam Pemecahan Masalah Matematika Ditinjau dari Perbedaan Gender - Jati Putri Asih Susilowati (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2016)
This research describes reasoning behind gender difference on problem solving. Subject of this reseach are two grade VIII students (male and female). Data in this research was analyzed using time triangulation. The reasoning based on student’s logic. Result of this study indicates that profile of reasoning junior high school students in solving math problems. For male, (1) understanding problems given, (2) linking the problems with the understanding of previously owned, (3) linking understanding possessed by the problems, and (4) conducting re-examination of the results obtained, but for female, (1) understanding the given problem, (2) planning problem solving by linking the formula that has been owned by the problems encountered, (3) implementing a plan of problem solving and reveal the reasons to use the formula, and (4) checking the solution obtained by checking the answer back.